Cognitive deficits after general anaesthesia in animal models: a scoping review. (February 2023) - Guo, Ling Yi; Kaustov, Lilia; Brenna, Connor T.A.; Patel, Vikas; Zhang, Cheng; Choi, Stephen; Halpern, Stephen; Wang, Dian-Shi; Orser, Beverley A.
Abstract: Background: It remains controversial whether general anaesthetic drugs contribute to perioperative neurocognitive disorders in adult patients. Preclinical studies have generated conflicting results, likely because of differing animal models, study protocols, and measured outcomes. This scoping review of preclinical studies addressed the question: 'Do general anaesthetic drugs cause cognitive deficits in adult animals that persist after the drugs have been eliminated from the brain?' Methods: Reports of preclinical studies in the MEDLINE database published from 1953 to 2021 were examined. A structured review process was used to assess original studies of cognitive behaviours, which were measured after treatment (≥24 h) with commonly used general anaesthetic drugs in adult animals. Results: The initial search yielded 380 articles, of which 106 were fully analysed. The most frequently studied animal model was male (81%; n =86/106) rodents ( n =106/106) between 2–3 months or 18–20 months of age. Volatile anaesthetic drugs were more frequently studied than injected drugs, and common outcomes were memory behaviours assessed using the Morris water maze and fear conditioning assays. Cognitive deficits were detected in 77% of studies ( n =82/106) and were more frequent in studies of older animals (89%), after inhaled anaesthetics, and longer drug treatments. Limitations of the studies included a lack of physiological monitoring, mortality data, and risk of bias attributable to the absence of randomisation and blinding. Conclusions: Most studies reported cognitive deficits after general anaesthesia, with age, use of volatile anaesthetic drugs, and duration of anaesthesia as risk factors. Recommendations to improve study design and guide future research are presented.